Refugees in Egypt: State Framing, Ministerial Narratives, and the Politics of Representation on Social Media - Kohail, Habiba (AUC Knowledge Fountain, 2026)
This study examines Egyptian government discourse on refugees in 2024, a year characterized by heightened regional displacement and the enactment of Egypt’s first Asylum Law (Law No. 164 of 2024). Using a multidisciplinary framework that combines framing analysis with van Dijk's socio-cognitive approach, the study systemically analyzes how the government construct refugees on social media and sets the boundaries of their inclusion in Egypt. The thesis analyzes the Egyptian government discourse on refugees across official social media platforms from January 1, 2024, to December 31, 2024, a period that witnessed an increase in the government engagement in the refugee issue as a result of the growing number of refugees and asylum seekers in Egypt that have exceeded one million. The corpus consists of 110 social media post published by two government entities: the Egyptian Cabinet and the Ministry of Foreign Affairs, Emigration and Egyptian Expatriates (MoFA). Employing a mixed-methods approach, the study quantitatively examines dominant frames, the frequency of descriptive elements, and the conflation of the terms “refugees” and “migrants.” This is complemented by qualitative critical discourse analysis (CDA), which investigates lexical choices, metaphors, macro- and micro-structures, and underlying political ideologies in line with Van Dijk’s socio-cognitive model. Through this approach, the study identifies dominant political ideologies in discourse and analyzes how they shape policy orientations and define the boundaries of refugees’ inclusion in Egypt. Key findings from the analysis include the identification of 423 distinct frames, with the Capacity and Resource Frame, External Regulation and Reputation Frame, and Economic Frame emerging as the most dominant in government discourse. Analysis of lexical choices revealed frequent conflation of the terms “refugees” and “migrants”, alongside repeated references to the number of refugees. Further ideological examination highlighted a strategic use of positive self-representation coupled with negative other representation, reflecting how the government frames its own role and actions in managing refugee issues and its political priorities regarding the topic.